1995
DOI: 10.1002/j.1460-2075.1995.tb07128.x
|View full text |Cite
|
Sign up to set email alerts
|

A major role for the protein tyrosine kinase JAK1 in the JAK/STAT signal transduction pathway in response to interleukin-6.

Abstract: The protein tyrosine kinases JAK1, JAK2 and Tyk2 and STATs (signal transducers and activators of transcription) 1 and 3 are activated in response to interleukin‐6 (IL‐6) in human fibrosarcoma cells. In mutant cells lacking JAK1, JAK2 or Tyk2, the absence of one kinase does not prevent activation of the others; activation does not, therefore, involve a sequential three‐kinase cascade. In the absence of JAK1, the phosphorylation of the gp130 subunit of the IL‐6 receptor and the activation of STATs 1 and 3 are gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
289
0
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(305 citation statements)
references
References 43 publications
13
289
0
3
Order By: Relevance
“…2C4 and ␥2A were maintained in 400 g/ml G418, and U1D and U4A were maintained in Hygromycin (250 g/ml). U4A cells stably transfected with JAK1 (U4/J1) or JAK2 (U4/J2) were maintained in both G418 and Hygromycin at the above concentrations (50). U4A cells stably transfected with TYK2 (U4/T2) were maintained in Hygromycin (as above) and Puromycin (0.5 g/ml).…”
Section: Methodsmentioning
confidence: 99%
“…2C4 and ␥2A were maintained in 400 g/ml G418, and U1D and U4A were maintained in Hygromycin (250 g/ml). U4A cells stably transfected with JAK1 (U4/J1) or JAK2 (U4/J2) were maintained in both G418 and Hygromycin at the above concentrations (50). U4A cells stably transfected with TYK2 (U4/T2) were maintained in Hygromycin (as above) and Puromycin (0.5 g/ml).…”
Section: Methodsmentioning
confidence: 99%
“…We next examined whether Isl1 interacted with the full-length Jaks. We chose Jak1 for further studies because Jak1 plays a predominant role in the IL-6 signaling (Guschin et al, 1995). We found that Isl1 bound to the full-length Jak1 but not to a kinase-inactive Jak1 ( Figure 1B).…”
Section: Identification Of Isl1 As a Jak Interacting Proteinmentioning
confidence: 99%
“…Downstream pathways of signal transduction and gene modulation by IL-6 which are activated by gp130 dimerization include activation of tyrosine kinases Jak1, Jak2 and Tyk2 (Guschin et al, 1995;Narazaki et al, 1994;Stahl et al, 1994), but also of Btk, Tec and Fes (Matsuda et al, , 1995, as well as activation of MAP kinase-dependent pathways (Akira et al, 1995). Several Signal Transducer and Transcriptional Activator (Stat) proteins are phosphorylated in response to IL-6 including gp130-bound Stat3/APRF (Akira et al, 1994;Harroch et al, 1994b;Zhong et al, 1994;Stahl et al, 1995) as well as Stat1 (Harroch et al, 1994a,b;Zhong et al, 1994) and Stat5b (Ripperger et al, 1995).…”
Section: Introductionmentioning
confidence: 99%